Physical activity and fitness in the community: the Framingham Heart Study. (26th August 2021) - Nayor, Matthew; Chernofsky, Ariel; Spartano, Nicole L; Tanguay, Melissa; Blodgett, Jasmine B; Murthy, Venkatesh L; Malhotra, Rajeev; Houstis, Nicholas E; Velagaleti, Raghava S; Murabito, Joanne M; Larson, Martin G; Vasan, Ramachandran S; et al.
Abstract: Aims: While greater physical activity (PA) is associated with improved health outcomes, the direct links between distinct components of PA, their changes over time, and cardiorespiratory fitness are incompletely understood. Methods and results: Maximum effort cardiopulmonary exercise testing (CPET) and objective PA measures [sedentary time (SED), steps/day, and moderate-vigorous PA (MVPA)] via accelerometers worn for 1 week concurrent with CPET and 7.8 years prior were obtained in 2070 Framingham Heart Study participants [age 54 ± 9 years, 51% women, SED 810 ± 83 min/day, steps/day 7737 ± 3520, MVPA 22.3 ± 20.3 min/day, peak oxygen uptake (VO2 ) 23.6 ± 6.9 mL/kg/min]. Adjusted for clinical risk factors, increases in steps/day and MVPA and reduced SED between the two assessments were associated with distinct aspects of cardiorespiratory fitness (measured by VO2 ) during initiation, early-moderate level, peak exercise, and recovery, with the highest effect estimates for MVPA (false discovery rate <5% for all). Findings were largely consistent across categories of age, sex, obesity, and cardiovascular risk. Increases of 17 min of MVPA/day [95% confidence interval (CI) 14–21] or 4312 steps/day (95% CI 3439–5781; ≈54 min at 80 steps/min), or reductions of 249 min of SED per day (95% CI 149–777) between the two exam cycles corresponded to a 5% (1.2 mL/kg/min) higher peak VO2 . Individuals with high (above-mean) steps or MVPA demonstrated above average peak VO2 values regardless of whether they had high or low SED. Conclusions: Our findings provide a detailed assessment of relations of different types of PA with multidimensional cardiorespiratory fitness measures and suggest favourable longitudinal changes in PA (and MVPA in particular) are associated with greater objective fitness. Graphical Abstract: